PREDIKSI KINERJA KARYAWAN BERDASARKAN PROSES TRAINER MENGGUNAKAN DATA MINING - Tri Utami, Yunita; Elisa, Erlin (LPPM Universitas Putera Batam, 2022)
There were many troubles which have found that it is difficult for HRD to predict employee performance because the HRD section can see data recap from the aspect of employee absenteeism or delay. The use of a structured application approach regarding data mining will be applied to determine which employees are entitled to receive prizes, as a result it will not be difficult for the company. C4.5 is used to determine which employees are entitled to receive rewards according to their own background, interests and abilities. The variables are checking work performance, employee discipline, targets that have been achieved, teamwork and ability to work. test and assessment results show that Decision Tree C4.5 is accurate to determine which employees are entitled to get rewards from the company